Adaptasi Mahasiswa Keperawatan Angkatan 2020 Di Salah Satu Universitas Swasta Indonesia Bagian Barat - Tahulending, Peggy; Panggabean, Defitaria; Panglipur, Riris Jatining; Zeva, Suge Tertia Orlen; Sudarja, Kusman (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2023)
Background: Adaptation is important for adjustment to change. A student who is pursuing education needs the ability to cope with the changes that occur. Students' inability to adapt has an impact on academic, social adjustment, personal-emotional adjustment, and institutional attachment. Purpose: To describe the adaptation nursing student class of 2020 at one of the Western Indonesian Private Universities. Methods: This study uses a quantitative descriptive method with a cross sectional approach. Population in this study 231 students. Instruments used adapted from the Student Adjustment to College Questionnaire (SACQ). The data analysis technique used is univariate analysis with conducting data from January to April 2022. Results: adaptation of nursing students class of 2020 in college at one of the western Indonesian private universities shows that 147 students obtained moderate results on the four subscales, first academic adjustment (66.7%), social adjustment (81%), personal-emotional adjustment (68%), and institutional attachment (57.8%). Students' Academic Adjustment abilities showed the highest percentage (19.7%) among others subscale and Institutional Attachment abilities showed the lowest percentage (29.3%). Conclusion: Students have a fairly good adaptation in adapting to the four subscales, but some students are still in the low category who show difficulties in adapting so it is necessary to form a special basic training program that discusses how to adapt appropriately in the university environment.